1992
DOI: 10.1099/0022-1317-73-12-3289
|View full text |Cite
|
Sign up to set email alerts
|

Bovine coronavirus spike glycoprotein: localization of an immunodominant region at the amino-terminal end of S2

Abstract: We have identified the binding site of monoclonal antibodies (MAbs) against the $2 subunit of the bovine coronavirus spike (S) glycoprotein. The location of this site was first investigated by using prokaryotic expression of DNA restriction fragments covering the entire S gene. The amino acid sequence containing the antibody binding site was shortened from 70 to 20 amino acids by digestion of plasmid DNA with exonuclease III, followed by sequencing of the smallest digestion product encoding an immunoreactive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Because the S protein is too large to be produced efficiently in E. coli, we prepared truncated molecules of the S protein, including the N-terminal S1 subunit, the C-terminal S2 subunit, and the middle part, designated Smid. In previous studies of MHV (3,16), bovine coronavirus (22), and severe acute respiratory syndrome coronavirus (15,26), this middle region was identified as an immunodominant linear neutralization domain by analysis using a prokaryotic protein expression system and monoclonal antibodies or patients' sera. As a result, large amounts of the His-tagged S1, S2, and Smid proteins were produced as insoluble proteins and were solubilized in a high-molar urea solution.…”
Section: Discussionmentioning
confidence: 99%
“…Because the S protein is too large to be produced efficiently in E. coli, we prepared truncated molecules of the S protein, including the N-terminal S1 subunit, the C-terminal S2 subunit, and the middle part, designated Smid. In previous studies of MHV (3,16), bovine coronavirus (22), and severe acute respiratory syndrome coronavirus (15,26), this middle region was identified as an immunodominant linear neutralization domain by analysis using a prokaryotic protein expression system and monoclonal antibodies or patients' sera. As a result, large amounts of the His-tagged S1, S2, and Smid proteins were produced as insoluble proteins and were solubilized in a high-molar urea solution.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the viral protein recognized by mAb 4H4, the binding of 4H4 in western blotting assays was examined. The assays showed that in the absence of 2-ME, the mAb 4H4 bound to a 105-kDa protein, which was identified as the S1 subunit of the S protein [34]. In the presence of 2-ME, the mAb 4H4 did not bind to any antigen (Fig.…”
Section: Sds-page and Western Blottingmentioning
confidence: 94%
“…The putative receptor-binding domain (so called C-domain spanning amino acid residues 326-540) is coloured blue and green. of the S1 subunit of BCoV and the N-terminus of the S2 subunit spanning amino acid residues 769-798 have been previously recognized using mAbs (Vautherot et al, 1992a;Yoo et al, 1991b). A polymorphic region spanning amino acid residues 456-592 has also been shown by sequence analysis of BCoV strains (Rekik & Dea, 1994).…”
Section: Positive Selection On the S Proteinmentioning
confidence: 99%